Preoperative plasma D-dimer level is a useful prognostic marker in ovarian cancer. (2nd January 2020) - Yamada, Yuki; Kawaguchi, Ryuji; Iwai, Kana; Niiro, Emiko; Morioka, Sachiko; Tanase, Yasuhito; Kobayashi, Hiroshi
Abstract: A high pre-treatment plasma D-dimer level was recently identified as a poor prognostic factor in several malignancies. The aim of this study was to evaluate the prognostic significance of plasma D-dimer levels in epithelial ovarian cancer (EOC). Data of 199 patients were retrospectively analysed. The relationships between pre-treatment D-dimer levels and other clinical parameters and prognosis were evaluated. Univariate analysis identified age, pre-treatment plasma D-dimer level, massive ascites, residual tumours, pre-treatment CA125 level, histological type, and FIGO stage as predictors of overall survival. The multivariate analysis showed that a high pre-treatment plasma D-dimer level ( p =.017), residual tumours ( p  < .001), and FIGO stage ( p  = .036) were independent risk factors of overall survival. Venous thromboembolism (VTE) did not influence overall survival ( p =.091). High pre-treatment D-dimer levels are associated with a poor prognosis independent of VTE status in EOC patients, and might be a useful prognostic biomarker. Impact statement: What is already known on this subject? In recent years, a high pre-treatment plasma D-dimer level has been identified as a prognostic factor in several malignancies, but only a handful of studies have assessed the role of pre-treatment plasma D-dimer levels in patients with EOC patients. Thus, the clinical significance and prognostic value of the plasma D-dimer level in EOC remain controversial, and there is also debate related to the association of the higher mortality rate among cancer patients with elevated D-dimer levels with VTE. What do the results of this study add? In our study, high pre-treatment D-dimer levels are associated with a poor prognosis independently of VTE in EOC patients. What are the implications of these findings for clinical practice and/or further research? The D-dimer level might emerge as a valuable prognostic biomarker, which will help doctors in the choice of initiating a more aggressive therapy, the combination of chemotherapy with anticoagulation therapy.